Simulation Training Is Useful for Shortening the Decision-to-Delivery Interval in Cases of Emergent Cesarean Section. Issue 1 (January 2019) - Iitani, Yukako; Tsuda, Hiroyuki; Ito, Yumiko; Moriyama, Yoshinori; Nakano, Tomoko; Imai, Kenji; Kotani, Tomomi; Kikkawa, Fumitaka
Abstract : (Abstracted from J Matern Fetal Neonatal Med 2018;31(23):3128–3132) In the setting of obstetric emergencies for pregnant women or their fetuses, prompt delivery should be performed. While no clear absolute time threshold has been demonstrated to be a specific standard of care, many guidelines have recommended that the decision-to-delivery interval (DDI) be kept to less than 30 minutes when emergent cesarean section (ECS) is performed.